If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(y+8)=6(y+8
We move all terms to the left:
6(y+8)-(6(y+8)=0
We multiply parentheses
6y-(6(y+8)+48=0
| 0.02x+2.4=2 | | 100-7x=4x+1 | | 2y÷5-3=10 | | -5/6k=-10/1 | | 8x-1=8(x-6) | | 3/4+n=1/2 | | x+0.1x=2077 | | 10x+5=3(5x+6) | | 9-(2n-3)=4-3n | | x-62=5 | | 7x+11=35-3x | | x-2.3=15.05 | | x–2.3=15.05 | | -42+x=-21 | | 7(2+w)=65(5+w) | | 53+y=72 | | 5x-10=x+20, | | 4x÷7=24 | | 3(5x+9)=162 | | 2x+7/6+x+8/6=x+7/4 | | F(x)=2x+3/4x4+9 | | 14k2-67k+63=0 | | 8.2z=24.6 | | 233280=5(6)^(1/3)x+2 | | 3x^2(x+7)(7x-15)^=0 | | 12x+47+7x=180 | | 3-(5-x=3-4x) | | 4(9+2x)=124 | | -9(x-7)=81 | | x^2-17x+136=0 | | 19=2.5/x | | 4(+2x)=124 |